Lived Experiences of Malayali Third Culture Children in GCC Nations: Qualitative Study - Bhadana, Krishna Gopal; Kumar, Sunil (Journal of Educational Research and Policies, 2025)
Third Culture Kids (TCKs) are becoming increasingly relevant as globalization and cultural mobility increase. The phenomena represents a unique convergence of cultural experiences, yet there is still a lack of information of the specific problems and resilience characteristics connected with these demographics. This study explores the experiences of Malayali TCKs residing in Gulf Cooperation Council (GCC) countries, providing insights into their cultural adaptation, sense of belonging, and intercultural competence. Using in- depth interviews and thematic analysis and utilizing phenomenological approach, the study delves into the subjective experiences, perspectives, and meanings attached to their cultural identity and affiliations. The findings offer valuable perspectives for counseling psychologists to create culturally sensitive interventions that support TCKs’ psychological well-being and cultural competence. Finally, the study contributes to fostering cross-cultural understanding and promoting social cohesion in multicultural societies for Malayali TCKs and other multicultural individuals in GCC societies.